Paw Skin as a Translational Model for Investigating Fibrotic and Inflammatory Wound Healing Defects in Recessive Dystrophic Epidermolysis Bullosa - DE GREGORIO CONCHA, CRISTIAN ALEJANDRO; Giselle Ramos-Gonzalez; Bernardo Morales-Catalán; EZQUER, EDUARDO FERNANDO; EZQUER, EDUARDO MARCELO (MDPI AG, 2025)
Recessive dystrophic epidermolysis bullosa (RDEB) is a severe genetic disease caused by COL7A1 mutations. It leads to skin fragility, chronic inflammation, and impaired wound healing. The condition often results in fibrotic scarring, pseudosyndactyly, and cutaneous squamous cell carcinoma (SCC). However, current animal models fail to fully replicate chronic RDEB wounds. In this study, we used Collagen VII-hypomorphic mice (Col7a1flNeo/flNeo) and created full-thickness wounds on their paw skin, an area prone to fibrosis due to mechanical stress. We analyzed the healing process using histology, immunofluorescence, and electron microscopy. The RDEB mice showed delayed wound closure, increased inflammation, and poor granulation tissue formation. At 30 days post-injury, we observed persistent fibrosis, with elevated levels of Collagen I, α-SMA+ myofibroblasts, and tenascin-C. These mice also had fewer intraepidermal nerve fibers, which may help explain the neuropathic pain associated with RDEB. Our model reproduces the main features of chronic RDEB wounds. It offers a useful tool for evaluating therapies aimed at reducing inflammation, fibrosis, and tumor risk in these patients.
Keywords: animals; collagen type vii; disease models; animal; epidermolysis bullosa dystrophica; fibrosis; inflammation; mice; skin; wound healing; collagen type 1; collagen type 7; tenascin; col7a1 protein; mouse; collagen type 7; animal experiment; animal model; animal tissue; article; collagen fiber; controlled study; dermoepidermal junction; electron microscopy; epidermolysis bullosa dystrophica; granulation tissue; histology; immunofluorescence; immunohistochemistry; inflammation; male; mechanical stress; mouse; myofibroblast; nerve fiber; neuropathic pain; nonhuman; paw skin; scar formation; scar tissue; sensory nerve; skin fibrosis; squamous cell skin carcinoma; transmission electron microscopy; wound closure; wound healing; wound healing impairment; animal; disease model; fibrosis; genetics; metabolism; pathology; skin; inflammation; paw skin model; rdeb; sensory nerve alteration; skin fibrosis; wound healing